Analysis of diabetic patients hospitalizations in Poland by gender, age and place of residence - Paweł Goryński; Bożena Moskalewicz; Wojciech Seroka (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. There are few updated data on rates of hospital mortality of diabetic patients and length of their hospital stay on a country level. To determine such rates we provided analysis using claims data from a Nationwide General Hospital Morbidity Study carried out by the National Institute of Public Health - National Institute of Hygiene (NIPHNIH) in Warsaw from 2010 to 2018. Objective. The aim of the study was to analyze the nine years changes of in-hospital morbidity and mortality in diabetic patients and length of hospital stay using a comparative approach by gender, age and place of residence. Material and methods. The data on all patients from general hospitals in Poland treated because of diabetes were taken from a nationwide database, kept since 1979 by the Department for Monitoring and Analyses of Population Health of NIPH-NIH. This database contains information gathered under the Statistical Research Program of Public Statistics. Hospitalization rates were used to evaluate the 'hospitalized' incidence of diabetes (number of hospitalization cases due to diabetes per year by the analyzed unit of population). In-hospital mortality was calculated as the percentage of deceased patients out of all patients hospitalized due to diabetes. Results. The number of cases and hospitalization rates of diabetic patients was rapidly declining by 18.8% for type 2 (E11) and 23.7% for type 1 (E10) diabetes. The downward tendency in the scope of hospitalization affected mainly older women and rural residents. Hospital mortality due to diabetes rose up dangerously to 3.77% exceeding the rates recorded eight years earlier. Conclusions. The recent reduction in hospitalization rates of people with diabetes in Poland may be associated with an unexpected increase in hospital mortality.